Market Place of Belgian Village and the Folk Dancers
The Belgian Village is at Twenty-third Street and Lief Erickson Drive, and portrays Belgium of the Middle Ages and the Renaissance period. In the center of the village is a market place where folk dances are held. The buildings are full replicas of architecture four centuries old, except that of the fish market of Ghent, which dates back to 1650. Included are the gateway of Ostend, built in 1400, a city gate of mediaeval Bruges, and a French Gothic church in Antwerp.